Oral Co-Supplementation of Curcumin, Quercetin, and Vitamin D3 as an Adjuvant Therapy for Mild to Moderate Symptoms of COVID-19—Results From a Pilot Open-Label, Randomized Controlled Trial - Khan, Amjad; Iqtadar, Somia; Mumtaz, Sami Ullah; Heinrich, Michael; Pascual-Figal, Domingo A.; Livingstone, Shona; Abaidullah, Sajid (Frontiers in Pharmacology, 2022)
Background: Curcumin, quercetin, and vitamin D3 (cholecalciferol) are common natural ingredients of human nutrition and reportedly exhibit promising anti-inflammatory, immunomodulatory, broad-spectrum antiviral, and antioxidant activities. Objective: The present study aimed to investigate the possible therapeutic benefits of a single oral formulation containing supplements curcumin, quercetin, and cholecalciferol (combinedly referred to here as CQC) as an adjuvant therapy for early-stage of symptomatic coronavirus disease 2019 (COVID-19) in a pilot open-label, randomized controlled trial conducted at Mayo Hospital, King Edward Medical University, Lahore, Pakistan. Methods: Reverse transcriptase polymerase chain reaction (RT-PCR) confirmed, mild to moderate symptomatic COVID-19 outpatients were randomized to receive either the standard of care (SOC) (n = 25) (control arm) or a daily oral co-supplementation of 168 mg curcumin, 260 mg quercetin, and 9 µg (360 IU) of cholecalciferol, as two oral soft capsules b.i.d. as an add-on to the SOC (n = 25) (CQC arm) for 14 days. The SOC includes paracetamol with or without antibiotic (azithromycin). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RT-PCR test, acute symptoms, and biochemistry including C-reactive protein (CRP), D-dimer, lactate dehydrogenase, ferritin, and complete blood count were evaluated at baseline and follow-up day seven. Results: Patients who received the CQC adjuvant therapy showed expedited negativization of the SARS-CoV-2 RT-PCR test, i.e., 15 (60.0%) vs. five (20.0%) of the control arm, p = 0.009. COVID-19- associated acute symptoms were rapidly resolved in the CQC arm, i.e., 15 (60.0%) vs. 10 (40.0%) of the control arm, p = 0.154. Patients in the CQC arm experienced a greater fall in serum CRP levels, i.e., from (median (IQR) 34.0 (21.0, 45.0) to 11.0 (5.0, 16.0) mg/dl as compared to the control arm, i.e., from 36.0 (28.0, 47.0) to 22.0 (15.0, 25.0) mg/dl, p = 0.006. The adjuvant therapy of co-supplementation of CQC was safe and well-tolerated by all 25 patients and no treatment-emergent effects, complications, side effects, or serious adverse events were reported. Conclusion: The co-supplementation of CQC may possibly have a therapeutic role in the early stage of COVID-19 infection including speedy negativization of the SARS-CoV-2 RT-PCR test, resolution of acute symptoms, and modulation of the hyperinflammatory response. In combination with routine care, the adjuvant co-supplementation of CQC may possibly help in the speedy recovery from early-stage mild to moderate symptoms of COVID-19. Further research is warranted. Clinical Trial Registration:Clinicaltrials.gov, identifier NCT05130671